Personalised housing support to improve health and well-being: findings from a local pilot programme in Yorkshire, England. Issue 1 (2nd January 2020) - Warwick-Booth, Louise; Coan, Susan; Bagnall, Anne-Marie
ABSTRACT: The contribution that housing associations have made to public health in recent years is recognised within research and policy literature. This paper examines a partnership pilot intervention implemented by one housing association and one community healthcare service provider that aimed to improve the health and well-being of people with complex needs living in social housing stock in one area in England. The pilot delivered co-commissioned personalised support using a holistic model of care. This paper describes the pilot intervention and associated findings drawn from a mixed methods evaluation. The findings illustrate positive service user reports, including improved health and well-being, increased independence and reduced social isolation. The intervention was also associated with reduced use of community health-care services; with an estimated potential local net saving of £20, 818 during the year of the pilot. In conclusion, this small-scale pilot intervention supported clients with complex health needs whilst reducing demands on community health-care services. Despite more research being needed in this area, particularly from larger and longer-term studies, this paper contributes to the evidence base by illustrating an effective health and housing practice-based partnership approach.